Drought and high temperature resistance evaluation of Dactylis glomerata L. - Salis M.; Carroni A.M.; Pitzalis M.; Sulas L.; Ledda L. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
With the aim to identify cultivars characterized by high drought and temperature resistance and high water use efficiency a study was carried out on 1 accession (Jana) and 4 Sardinian ecotypes of orchard grass (Dactylis glomerata L.) (Bolotana, Bonorva, Bonnanaro, Platamona). To evaluate the adaptive responses of different D. glomerata ecotypes, two trials were carried out in order to evaluate drought resistance under rain proof shelter and controlled water supply, and to evaluate high temperature resistance in a greenhouse where high summer temperature (daily maximum temperature > 50 °C) were monitored. On December 2010 seeds were sown in seed benches at the beginning of March the plants were transplanted at the 5th leaf stage in 45 litres pots, utilized in the drought resistance trial, and in a container (25 x 0.8 m), utilized in the high temperature resistance trial. In drought resistance trial, two water regimes were applied: 1) Control, soil humidity was kept at the field capacity, 2) W1, pots water losses were reintegrated at 80%. Above ground plant biomass, net photosynthesis, transpiration rate, stomatal conductance, leaf relative water content (RWC) were monitored throughout both trials.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)